Analysis Of Rent-Based Capital Loan Contracts From a Sharia Law Perspective - Maimuna, Siti; Sabrina, Nor Alfaini; Mafula, Wildaniyah (Universitas Trunojoyo Madura, 2022)
The purpose of this study is to review and evaluate the implementation of capital loan contracts in Islamic microfinance practices. This study contributes theoretically and practically to the development of sharia law, especially the implementation of capital loan contracts in sharia microfinance. The research method used is qualitative research with a field research approach. The object of this research is a sharia capital loan contract in the program to build a prosperous family economy in PNM Mekar. Primary data were obtained through interviews and analyzed comprehensively with qualitative sharia contracts. The study results found that the practice of capital loans differed from Islamic Law because there were indications of prohibited interest practices and the practice of gharar in the operational procedures of capital loans.